Human Sepsis Eicosanoid and Proresolving Lipid Mediator Temporal Profiles: Correlations With Survival and Clinical Outcomes - Dalli, Jesmond; Colas, Romain A; Quintana, Carolina; Barragan-Bradford, Diana; Hurwitz, Shelley; Levy, Bruce D; Choi, Augustine M; Serhan, Charles N; Baron, Rebecca M (Critical care medicine, 2017)
To identify and measure recently described chemical mediators, termed specialized pro-resolving mediators that actively regulate the resolution of acute-inflammation, and correlate measurements with clinical outcomes. Herein, deidentified plasma was collected from sepsis patients (n = 22 subjects) within 48 hours of admission to the ICU and on days 3 and 7 thereafter and subjected to lipid mediator profiling. Brigham and Women's Hospital Medical Intensive Care Unit. Patients in the medical ICU with sepsis. In all patients, we identified more than 30 bioactive mediators and pathway markers in peripheral blood using established criteria for arachidonic acid, eicosapentaenoic acid, and docosahexaenoic acid metabolomes. These included inflammation initiating mediators leukotriene B4 and prostaglandin E2 and pro-resolving mediators resolvin D1, resolvin D2, and protectin D1. In sepsis nonsurvivors, we found significantly higher inflammation-initiating mediators including prostaglandin F2α and leukotriene B4 and pro-resolving mediators, including resolvin E1, resolvin D5, and 17R-protectin D1 than was observed in surviving sepsis subjects. This signature was present at ICU admission and persisted for 7 days. Further analysis revealed increased respiratory failure in nonsurvivors. Higher inflammation-initiating mediators (including prostaglandin F2α) and select proresolving pathways were associated with the development of acute respiratory distress syndrome, whereas other traditional clinical indices were not predictive of acute respiratory distress syndrome development. These results provide peripheral blood lipid mediator profiles in sepsis that correlate with survival and acute respiratory distress syndrome development, thus suggesting plausible novel biomarkers and biologic targets for critical illness.